2017
DOI: 10.18203/2349-2902.isj20171138
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbilirubinemia as a predictor of the severity of acute appendicitis - an observational study

Abstract: Background: Appendicitis is the most common acute abdominal condition requiring emergency surgery, with a lifetime risk of 6%. Appendectomy continues to be one of the commonest procedures in general surgery, accounts for approximately 1% of all surgical operation. Despite the increased use of ultrasonography, computed tomography scanning and laparoscopy, the rate of misdiagnosis of appendicitis has remained constant (15.3%). The aim of this study was to whether Serum Bilirubin can be considered as a new labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…According to this study bilirubin more than 1 mg/dl was seen in 2 (3.4%), 25 (43.2%) and 31 (53.4%) of cases respectively with p value less than 0.05 and over all sensitivity of 94$, specificity of 66.66%, PPV of 88.5% and NPV of 80%. 26 In another study by Estrada et al odd ration see for association of hyperbilirubinemia with perforated appendicitis was seen as 2.96 (95% CI, 1.11-7.6) with p value of 0.031. 27 According to a retrospective analysis done by Emmanuel et al in 2011 found that hyper bilirubinemia was significantly high in cases that presented with mean longer duration of time with p value of 0.001 and specificity was seen in 88% of the cases.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to this study bilirubin more than 1 mg/dl was seen in 2 (3.4%), 25 (43.2%) and 31 (53.4%) of cases respectively with p value less than 0.05 and over all sensitivity of 94$, specificity of 66.66%, PPV of 88.5% and NPV of 80%. 26 In another study by Estrada et al odd ration see for association of hyperbilirubinemia with perforated appendicitis was seen as 2.96 (95% CI, 1.11-7.6) with p value of 0.031. 27 According to a retrospective analysis done by Emmanuel et al in 2011 found that hyper bilirubinemia was significantly high in cases that presented with mean longer duration of time with p value of 0.001 and specificity was seen in 88% of the cases.…”
Section: Discussionmentioning
confidence: 93%
“…6 Approximately 50% of cases of gangrenous or perforated appendicitis are associated with a faecolith in contrast with DOI: 10.29309/TPMJ/2019. 26 2 uncomplicated appendicitis in which a faecolith is rarely present. 7 Most of the cases of acute appendicitis are diagnosed by Alvarado score 7 and above.…”
Section: Introductionmentioning
confidence: 99%
“…The mean age of presentation being 30.7±12.2 years in males and 30.8±14.1 years in females respectively, this was consistent with the quoted incidence of Appendicitis in the literature where it is most frequently seen in patients in their second through fourth decades of life. 17 In our study population of 100 patients, 75 patients (75%) were diagnosed as acute appendicitis pre-operatively while 25 patients (25%) were diagnosed with appendicular perforation. On confirmation with histopathological reports (HPR) post-operatively 59 patients (59%) were acute appendicitis case and 41 patients (41%) of appendiceal perforation as diagnosis.…”
Section: Discussionmentioning
confidence: 80%
“…Cheekuri et al in 2017 conducted a prospective study Hyperbilirubinemia as a predictor of the severity of acute appendicitis-an observational study with sample size of 110 showed results of sensitivity 94%, specificity 66%, PPV 88.5%, NPV 80%. 1 D'souza et al conducted a prospective study Bilirubin; a diagnostic marker for appendicitis with sample size of 143 showed results of sensitivity 70%, specificity 82%, PPV 47%, NPV 93%. 3 S. Khan in 2008 conducted a prospective study of total bilirubin levels in appendicitis with sample size of 110 showed a results of sensitivity 87%, specificity 100%, PPV 100%, NPV 17.3%.…”
Section: Discussionmentioning
confidence: 99%